2018
DOI: 10.3390/nu10101516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Consumption of Cocoa-Derived Products on Uric Acid Crystallization in Urine of Healthy Volunteers

Abstract: The purpose of this study was to determine the effects of consumption of different cocoa-derived products on uric acid crystallization in urine of 20 healthy volunteers. Participants were requested to select the specific diet that they wished to follow during the 12 h prior to collection of urine. The only restriction was that the diet could not include any product with cocoa, coffee, or caffeine. On the first day, each volunteer followed their selected diet, and an overnight 12 h urine sample was collected as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
1
20
0
2
Order By: Relevance
“…A high-purine diet, which is one of the risk factors for gout, is usually associated with a high-protein diet, such as seafoods, meats, viscera and so on [33,46]. In addition, HPD also elevated oxidative stress in rats and coupled with urate level increased in the cerebral cortex and hypothalamus in rats [47].…”
Section: Discussionmentioning
confidence: 99%
“…A high-purine diet, which is one of the risk factors for gout, is usually associated with a high-protein diet, such as seafoods, meats, viscera and so on [33,46]. In addition, HPD also elevated oxidative stress in rats and coupled with urate level increased in the cerebral cortex and hypothalamus in rats [47].…”
Section: Discussionmentioning
confidence: 99%
“…52 Thus, epicatechin and procyanidins seem to contribute in the maintenance of renal function and structure during diabetes. 17,33,35,42 In addition, theobromine alone can protect against uric acid crystallization, 53 and in combination with cocoa flavanols enhance their protective vascular effects, 54 which also seem to participate in the preservation of kidneys. It is also worth mentioning that, using the body surface area normalisation method, 55 the amount of cocoa employed in the present animal study is equivalent to a daily dose of 64.5 g cocoa, containing 1075 mg polyphenols, for a 60 kg human.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of 24 h urine were collected at baseline to verify satisfaction of the admission criteria and 2 h urine collected after overnight fasting at baseline and after each stage of treatment. Treatment efficacy was evaluated by a test specially designed to measure the ability of urine to inhibit the crystallization of UA (a risk of UA crystallization (RUAC) test) [ 14 ] and urinary theobromine was measured using HPLC (High Performance Liquid Chromatography), as previously described [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that dietary theobromine is a potent inhibitor of UA crystallization in humans [ 13 , 14 ]. Theobromine is abundant in chocolate and cocoa [ 15 ].…”
Section: Introductionmentioning
confidence: 99%